Analysis of Nature and Extent of Nutrition Education Imparted to the Rural School Children - Pal, Ankit; Dixit, Awadhesh; Kumar, Sunil; Alok Dube; Ashish Singh; Akanksha Singh (International Journal of Social Sciences Review, 2024)
With an emphasis on the responsibilities played by teachers, parents, and Anganwadi workers, this study intends to analyse the existing practises of nutrition teaching in rural schools in Bihar, India. An ex-post facto research design was used for the study, which was carried out in the Bihar district of Arwal. Teachers, parents, and Anganwadi staff made up the 240 participants who were drawn at random. Data collection was done using questionnaires, which were pretested for validity and reliability. As well as identifying any gaps or areas for improvement, the obtained data were analysed to ascertain the common tactics and methodology utilised by educators, parents, and Anganwadi staff in delivering nutrition education. According to the study, parents used a variety of tactics to promote healthy eating habits in their kids, including giving them choices, giving nutritious foods catchy names, and making food appealing to the eye. For nutrition teaching, teachers mostly used lectures, discussions, and visual aids like nutrition charts and posters.